Haemophilus Infections in Chickens : 2. Types of Haemophilus paragallinarum Isolates from Chickens with Infectious Coryza, in Relation to Haemophilus gallinarum Strain No.221 - SAWATA, Akira; NAKASE, Yasukiyo; KUME, Katsumi (The Japanese Journal of Veterinary Science, 1978)
Eighty-eight Haemophilus isolates derived from chickens with infectious coryza were classified. Then they were compared biologically and serologically with Haemophilus gallinarum type I and III of strain No.221 described by Kato et al., and with H. paragallinarum strain H-18 reported previously by the authors. Of the isolates, 86 were capsulated and biologically identified as H. paragallinarum. Of them, 62 strains were hemagglutinable and serologically identical with H. gallinarum type I of strain No.221 (H. paragallinarum serotype 1) and 24 strains unhemagglutinable and serologically identical with H. paragallinarum strain H-18 (H. paragallinarum serotype 2). All the capsulated strains corresponded to either serotype 1 or 2, which showed a similar degree of pathogenicity for chickens, irrespective of serotype. The remaining 2 isolates were noncapsulated and nonpathogenic, and identical with Kato's type III strain, which was a variant derived from capsulated H. paragallinarum serotype 1.